Impact of exercise interventions on cardiotoxicity in patients with breast cancer undergoing chemotherapy: a study protocol for a quasi-randomised controlled trial - Ran Wei; Yingjie Cai; Yufei Guo; Tieying Shi; Yuzhu Liu; Huiyan Cheng; Mi Li (BMJ Open)
Introduction Agents used in antitumour therapy have toxic effects on the cardiovascular system of breast cancer (BC) patients, increasing the risk of cardiovascular disease, which has become the most common non-cancer cause of death in BC patients. Exercise can effectively prevent or reduce the occurrence of cardiotoxicity, however, most BC patients have low levels of physical activity. The Health Action Process Approach (HAPA) model has been successfully applied to encourage patients to adhere to physical exercise. This study aims to explore the impact of exercise interventions based on the HAPA model on the monitoring indicators related to cardiotoxicity in BC patients during chemotherapy, aiming to prevent cardiotoxicity in BC patients and improve their physical activity level, exercise self-efficacy, exercise social support and exercise compliance.Methods and analysis In a protocol for a quasi-randomised controlled trial involving a 4-month intervention, 62 patients with BC will be recruited from a tertiary care centre in China. Participants from the first oncology department will be assigned to the HAPA model-based exercise intervention group (n=31), while participants from the second oncology department will be assigned to the control group that will receive standard exercise guidance (n=31). The primary outcome will be the incidence of cardiotoxicity assessed by Electrocardiogram (ECG). The secondary outcomes will include physical activity level, exercise self-efficacy, exercise social support and exercise compliance, which will be evaluated by the short form of the International Physical Activity Questionnaire (IPAQ-SF), Self-Efficacy for Exercise Scale (SEE), Social Support Scale for Exercise (SSSE), and percentage of achieving the recommended total time of exercise per week. The chi-square test or Mann-Whitney U tests will be applied to compare the differences in ECG results and exercise compliance between the two groups. To evaluate the effect of exercise intervention on IPAQ-SF, SSE and SSSE, repeated measures ANOVA will be employed to examine the group-by-time interactions and main effects.Ethics and dissemination This study has been approved by the Ethics Committee of the First Affiliated Hospital of Dalian Medical University (PJ-KS-KY-2024-267(X)). The results of this study will be published via peer-reviewed publications and presentations at conferences.Trail registration number ChiCTR2400090672.